Struktur komposisi vegetasi hutan pinus di Kawasan Candi Gedong Songo, Kecamatan Bandungan, Kabupaten Semarang, Jawa Tengah - Karina Natalia; Jumari Jumari; Murningsih Murningsih (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2020)
Indonesia as a country with many islands and a variety of fauna flora, as well as a wide area of conservation and tourism places. Gedong Songo Temple is a top tourist attraction in Semarang district that attracts many local and foreign tourists. Gedong Songo Temple has the most prominent vegetation that is pine forest that plays a role in the area of tourism and ecosystem. The purpose of this study is to examine the composition structure of pine forest vegetation in the Gedong Songo temple area. The method used in this study is a sampling method with a quadratic plot. The structure of the vegetation composition is done on trees, shrubs and perdu, and herbs. In the tree note the type name, the number of individuals, and the basal diameter of the area. In the bush, shrubs, and herbs are recorded type names, number of individuals, and covering. Vegetation analyses include density, dominancy, frequency, and index important values. The results of the study obtained a total of 32 plant species consisting of 24 families. At the tree level there are 3 species, the shrub level and the shrubs 19 species, and the herb level of 16 species. The highest tree-level INP value of pine is 208.8%, the INP value of the bush level and the highest shrubs of 107% coffee, and the highest herbal level INP value of 141%.